The Effect of Hydration on the Structure and Transport Properties of Confined Carbon Dioxide and Methane in Calcite Nanopores - Mohammed, Sohaib; Gadikota, Greeshma (Frontiers in Energy Research, 2018)
With increasing interest in using or displacing confined water for CH4 recovery or CO2 storage in nanoporous environments, understanding the organization and diffusion of gases is confined water environments is essential. In this study, the effect of hydration on the structure and diffusivity of confined carbon dioxide (CO2) and methane (CH4) in 2 nm slit-shaped calcite nanopore was studied using classical molecular dynamics simulations. The absence of confined water and the effect of different water concentrations including one layer of confined water composed of 150 water molecules, 500 water molecules, and 1,296 water molecules that correspond to the density of bulk water of 1 g/cm3 on the structural arrangement and diffusivity of confined CO2 and CH4 were investigated. Water molecules were found to influence the anisotropic distribution and mobility of confined CO2 and CH4 significantly by altering the structures of the adsorbed gas layers onto the calcite surfaces. The preferential adsorption of water on calcite surface over CO2 and CH4 resulted in the displacement of the adsorbed gas molecules toward the center of the pore. This water-induced displacement impacts the diffusivity of the confined gases by enabling transport through the center of the pore where there are fewer intermolecular collisions and less steric hindrance for transporting the molecules. Therefore, the diffusivity of CO2 and CH4 is higher in the presence of a single water layer as opposed to in pores without water. Energetic calculations showed that van der Waals and electrostatic interactions contributed to the affinity of CO2 for calcite surfaces, while van der Waals interactions dominate CH4 interactions with calcite and the surrounding water molecules. The anisotropic variations in the diffusivities of confined fluids emerge from changes in the organization of confined fluids and potential differences in the free energy distributions as a function of the orientation of the calcite surface. These findings suggest that any efforts to potentially engineer the nano-scale pore environment in calcite for enhanced gas recovery or storage will require us to consider the organization and anisotropic transport behaviors of confined fluids.